2019
DOI: 10.3390/medicina55070319
|View full text |Cite
|
Sign up to set email alerts
|

Invasive and Non-Invasive Fungal Rhinosinusitis—A Review and Update of the Evidence

Abstract: Fungal infections are a subset of infectious processes that an otolaryngologist is required to be familiar with. They can be encountered in otology, rhinology and head and neck surgery. The presence of fungal rhinosinusitis is well recognised by otolaryngologists, but the classifications and appropriate management are not so well understood. The prevalence of fungal sinus disease is thought to be have been increasing in recent decades There is speculation that this may be due to increased awareness, antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
198
3
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(215 citation statements)
references
References 40 publications
2
198
3
12
Order By: Relevance
“…Fungal rhinosinusitis refers to a wide variety of conditions that can present acutely in severely immunocompromised patients, or chronically in patients with mild immunosuppressive states such as diabetes mellitus or chronic corticosteroid use. 9 It is categorized as acute (less than 4 weeks) or chronic (greater than 4 weeks), and as noninvasive or invasive.…”
Section: Fungal Rhinosinusitismentioning
confidence: 99%
See 2 more Smart Citations
“…Fungal rhinosinusitis refers to a wide variety of conditions that can present acutely in severely immunocompromised patients, or chronically in patients with mild immunosuppressive states such as diabetes mellitus or chronic corticosteroid use. 9 It is categorized as acute (less than 4 weeks) or chronic (greater than 4 weeks), and as noninvasive or invasive.…”
Section: Fungal Rhinosinusitismentioning
confidence: 99%
“…fungal colonization, encountered in patients with anatomic abnormalities such as nasal polyps. 9 Fungal infections are also thought to have a role in the development of chronic rhinosinusitis. 10…”
Section: Frerichs and Brateanumentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that nystatin can be loaded into liposomes and administered intravenously to reduce toxicity while retaining its antifungal activity [3][4][5][6]. At present, there are no drug therapies of nystatin that can be used to treat non-invasive nasal aspergillosis, except for nasal irrigation [7,8]. Moreover, using permeation enhancers, the intranasal delivery of nystatin can perhaps be used to achieve drug concentration in systemic circulation, thus can be applied in treatment of systemic fungal infections [9].…”
Section: Introductionmentioning
confidence: 99%
“…Fungal (mycotic) infections represent one of the four major microbiological subgroups (bacteria, viruses, parasites, fungi) of human diseases [1]. Although there are thousands of different types of fungi, there are only a small number of fungi being clinically relevant.…”
Section: Introductionmentioning
confidence: 99%